(untitled) (Revista de Educação Continuada em Medicina Veterinária e Zootecnia do CRMV-SP, 2013)
The currently recommended by WHO for prevention individuals exposed to rabies virus (RV) is pre-exposure prophylaxis (PEP) through the administration of three doses of rabies vaccine by intradermal (ID) or intramuscular (IM) route. The previous study showed that the persistence of protective antibodies titer in the IM schedule is more long-lived, suggesting a different clearance mechanism of antibody. It known that carbohydrate modification of antibodies could induce accelerated clearance or modulate of antibody effector functions. All endogenous IgG antibodies contain an N-linked glycan in the Fc region and about 20% contain glycans elsewhere on the molecule to maintain the two heavy chains of the Fc in an open conformation required for interactions with activating Fcγ receptors (FcγRs).